EFL UNIVERSITY STUDENTS' PERCEPTION OF THE USE OF ONLINE LEARNING PLATFORM - Desy Try Rahayu Bagata (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2020)
Abstract: This study aims to describe the EFL university students’ perception of the use of online learning platform in the covid-19 pandemic and to examine the difference in students’ perception based on gender. The researcher conducted aquantitative using survey design method. The sample of this study was 80 students consists of 40 males and 40 females students of sixth year of the english education of Universitas Islam Malang. The instrument of this study was an online questionnaire by using a five-likert scale type. It uses to answer the students’ perception of the use of online learning platform. The result of the study showed that the EFL students’ perception of the use of online learning platforms share positive perception. The finding was also showed that there is a significant difference between male and female of the use of online learning platform. Male students’ perspective is more positive than females in the use of online learning platforms.Keywords: students’ perception, online learning platform, gender